Transformational Leadership and its Impact on Creative Behavior: A Study of the Opinion of a Sample of Decision Makers in the General Traffic Directorate - Kraidi Bunyan Alkabi, Makkiyah; Tarik Ahmed Salih Al-Qaisi, Dunya (International Journal of Engineering and Technology, 2018)
The purpose of this research is to determine the effect of transformational leadership in the creative behavior of decision makers in the Directorate of Public Traffic. The research problem was formulated in several questions focused on the statement of impact among its variables. The research was based on a main hypothesis, which was subjected to several tests to ascertain its validity. In order to achieve the objectives of the research, a questionnaire was developed which included (30) items to collect the data from the intentional sample of the research, with a total of (70) questionnaires, and the number of questionnaires valid for the analysis (67) of the total distributed questionnaires. The statistical program (SPSS) was used to analyze the data. The results are the most important: to drive the transformational leadership (ideal influence, inspirational motivation, intellectual arousal, individual legalism), which together have a significant effect on the creative behavior of the research sample members, and thus increase the attention to the positive strengths that form the transformational leadership contributes to the support and development of creative behavior of the organization, in question, to keep pace with progress in their field.Â